Penerapan Model Berbasis Proyek untuk Meningkatkan Partisipasi dan Hasil Belajar PKn Siswa SD - Kurniasih, Try Indiastuti; Lestari, Yulita Dwi; Andriani, Lucky (Program Studi PGSD, Jurusan Ilmu Pendidikan, STKIP PGRI Bandar Lampung, 2021)
This study aims to increase participation in the learning outcomes of elementary school students by using a project-based learning model in the sixth grade Citizenship Education subject at SD Negeri 2 Merak Batin, South Lampung. This type of Classroom Action Research (CAR) uses qualitative data, and the research used as a new research is a classroom action research model with Kemmis and Mc. Taggart which includes planning, action, implementation of action and observation, and reflection. The results of research conducted in class VI B SD Negeri 2 Merak Batin South Lampung, with the research subjects 25 students and homeroom teacher can be said to be running well. By applying the project-based learning model / Project Based Learning can increase the participation of student learning outcomes, this is evidenced by student learning outcomes that occur in Cycle I with an average of 75.76 and become 94.6 in Cycle II. By applying the project-based learning model / Project Based Learning according to the stages of the learning model, it can have a big influence on student activity in class.